Role of Suppressors of Cytokine Signaling 3 in Bone Inflammatory Responses - Gao, Anqi; Van Dyke, Thomas E. (Frontiers in Immunology, 2014)
Suppressor of cytokine signaling 3 (SOCS3) is a potent regulator of cytokine signaling in macrophages and T cells. In recent studies, evidence has been provided for SOCS3 activation in all major bone cells including osteoclasts, chondrocytes, synoviocytes, and osteoblasts. The investigation of SOCS3 function in bone remodeling systems implicates SOCS3 as a key signaling molecule in bone cell-mediated inflammatory responses. Both pro- and anti-inflammatory functions of SOCS3 have been demonstrated in different types of bone cells. This review provides an overview of the important role of SOCS3 in inflammatory responses of various bone cells and in bone inflammatory disorders such as periodontal disease and arthritis. Understanding the roles of SOCS3 in inflammatory diseases of bone and joints such as arthritis, osteomyelitis, and periodontal diseases is critical to revealing insights into signaling pathways that can be manipulated in potential therapeutic approaches.